DETERMINACIJA NEPRIJATELJA U DIREKTIVAMA GLAVNOG ŠTABA I VRHOVNE KOMANDE VOJSKE REPUBLIKE SRPSKE // DETERMINING THE IDENTITY OF THE ENEMY IN THE DIRECTIVES OF THE MAIN HEADQUARTERS AND THE HIGH COMMAND OF THE ARMY OF REPUBLIC OF SRPSKA - Mesud Šadinlija (Historijski pogledi, 2020)
Among the numerous open questions of contemporary historiography regarding the breakdown of Yugoslavia and its consequences, the issues connected to the post-Yugoslav wars still cause the most disputes. Even in the case of the war in Bosnia and Herzegovina, waged from 1992 to 1995, all of the important questions concerning its causes, character and consequences, are still considered open, whereby the dubious interpretative discourses are often constructed on the basis of an approach which is founded on the narrowing of the jointly observed historical phenomena. The attempts to construct and legitimize the corresponding particular interpretations of the character of the war in Bosnia and Herzegovina through a narrow and selective approach applied in the identifications of the warring sides and their mutual relations are not rare. In such situations the most reliable methodological approach in the framework of historical science is to return the focus from the level of interpretation to the historical sources, their analysis, determining the authenticity and relevance for the collection of issues in question. In this work we will dedicate our attention to the directives of the Main Headquarters and the High Command of the Army of Republic of Srpska issued during 1992-1995 in those parts in which these documents perform the identification and determination of the enemy.